2017
DOI: 10.1155/2017/6894374
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Subsets in Rheumatoid Arthritis Patients on Long-Term Anti-TNF or IL-6 Receptor Blocker Therapy

Abstract: Data on the impact of biological therapies on the T-cell phenotype in rheumatoid arthritis are limited. Here, we prospectively measured the percentages of 15 circulating T-cell subtypes using flow cytometry. We obtained transversal and longitudinal data in 30 anti-TNF responders, 19 secondary anti-TNF nonresponders, and 43 IL-6R antagonist responders, before, 8 weeks and at least 6 months after biological therapy. Untreated RA patients and healthy controls were also included. The important findings are the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
4
30
1
1
Order By: Relevance
“…There are many similarities in these results and our previous observations in RA patients [16]. The present measurements confirm our previous conclusions that the major mechanism of action of anti-TNF therapy is not the restoration of the activated immune system – observed in active disease – to a state similar to healthy individuals, in terms of the T-cell subset distribution.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There are many similarities in these results and our previous observations in RA patients [16]. The present measurements confirm our previous conclusions that the major mechanism of action of anti-TNF therapy is not the restoration of the activated immune system – observed in active disease – to a state similar to healthy individuals, in terms of the T-cell subset distribution.…”
Section: Discussionsupporting
confidence: 91%
“…The expansion of Th17 and Th1 cells has been described by other authors too [23, 24], and we observed a similar phenomenon in RA too [16]. A potential explanation has been presented by Notley et al [25], who have shown that anti-TNF treatment of mice in the collagen-induced arthritis model led to the upregulation of the p40 subunit of the IL-12/23 receptor and a resulting increase in both Th17 and Th1 cell frequencies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations